Development and clinical trials of psycho-audiological module (PAM) as an intervention for patients with tinnitus - Wan Salleh, Wan Suhailah Wan Husain (2016)
Tinnitus is a common symptom among otological patients and serious if untreated. The main focus of the present study was to develop a new intervention, known as Psycho- Audiological Module (PAM), for treating tinnitus. This study had three consecutive phases: Phase I was about determining the current tinnitus management by ORL specialists, audiologists and medical officers in Malaysia, Phase II was about the development and validation of PAM and the effectiveness of PAM intervention in treating patients with tinnitus (relative to broadband masker intervention, BBM) was studied in Phase III. In Phase I, 212 validated questionnaires were sent to 16 hospitals. A good response rate was obtained (51.8%) enabling detailed analysis of the survey outcomes. It was found that pure tone audiometry and tympanometry were the routine assessments performed in most ORL and audiology clinics for patients with tinnitus. Pharmacotherapy and hearing aid fitting were the most common treatments offered to the patients. Nevertheless, the majority of respondents were not satisfied with their current practice and they looked forward to have one standard guideline for managing patients with tinnitus in a more effective manner. In Phase II, the PAM was developed based on extensive literature review and discussions among the relevant experts including a clinical psychologist. It consists of four specific parts with the general aim to guide patients with tinnitus in the habituation process. The newly developed PAM was then validated by the experts and patients with tinnitus. In Phase III, a clinical trial to justify the effectiveness of PAM intervention to treat patients with tinnitus was carried out in 28 participants with complaint of tinnitus. The changes between pre- and post-intervention (2 weeks, 3 months and 6 months) sessions were assessed by Borang Evaluasi Soal selidik Tinnitus (BEST), Bahasa Malaysia Depression, Anxiety and Stress Scale 21 (BM DASS 21) and tinnitus psychoacoustic measures. While both interventions were found to be effective, the PAM intervention was superior in reducing tinnitus severity with a large effect size (r=0.531) relative to the control group (BBM, n=28) (r = 0.370). Furthermore, the effectiveness of PAM intervention was more evident by looking at the number of participants with clinical significant reduction in the perceived tinnitus severity. At 2 weeks after intervention, 32% of participants revealed clinical significant reduction and the number increased to 64% at 6 months follow-up. The PAM intervention was also effective in reducing perceived psychological symptoms. At 6 months follow-up, the number of participants with clinical significant reduction could be as high as 32%. On the other hand, no significant changes were seen in tinnitus loudness and minimum masking level in the PAM group. Due to its superior performance, PAM intervention should be used in clinical setting for managing patients with tinnitus in a structured manner.